2015
DOI: 10.1093/jme/tjv006
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Longipalpis (Diptera: Psychodidae) Complex Populations in Mato Grosso do Sul, Brazil

Abstract: Owing to the existence of cryptic species that are difficult to distinguish morphologically, the search for new taxonomic characters and methods for identifying and classifying sand flies continues. Lutzomyia longipalpis (Lutz & Neiva, 1912) and Lutzomyia cruzi (Mangabeira, 1938) (Diptera: Psychodidae) are two such species that occur in sympatry in some regions of Mato Grosso do Sul State (MS). Twenty females and twenty males from each of the five populations of Lu. longipalpis and one population of Lu. cruzi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
9
0
4
Order By: Relevance
“…A newer approach, geometric morphometric analysis, provides a mechanism to evaluate shape independent of size through the use of landmarks on two- and three-dimensional surfaces (Rohlf & Slice, 1990; Bookstein, 1991; Bookstein, 1996; Rohlf & Marcus, 1993; Dryden & Mardia, 1998). Geometric morphometric analysis has provided insight into patterns of morphological variation associated with Musca domestica L. wild populations and laboratory colonies (Ludoški et al, 2014), wild sandfly populations (Santos et al, 2015), the discrimination of four species of Culex mosquitoes (Laurito, Almirón & Ludueña-Almeida, 2015) and synonymy of two Bactrocera species (Schutze et al, 2015). Geometric morphometric analysis has also been instrumental in visualizing and comparing morphometric variation in relation to factors such as competition of sympatric species (Adams & Rohlf, 2000), environmental variables such as temperature and rainfall (Benítez et al, 2014), temporal variation (Drake & Klingenberg, 2008), and geographic variation (Lashkari et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A newer approach, geometric morphometric analysis, provides a mechanism to evaluate shape independent of size through the use of landmarks on two- and three-dimensional surfaces (Rohlf & Slice, 1990; Bookstein, 1991; Bookstein, 1996; Rohlf & Marcus, 1993; Dryden & Mardia, 1998). Geometric morphometric analysis has provided insight into patterns of morphological variation associated with Musca domestica L. wild populations and laboratory colonies (Ludoški et al, 2014), wild sandfly populations (Santos et al, 2015), the discrimination of four species of Culex mosquitoes (Laurito, Almirón & Ludueña-Almeida, 2015) and synonymy of two Bactrocera species (Schutze et al, 2015). Geometric morphometric analysis has also been instrumental in visualizing and comparing morphometric variation in relation to factors such as competition of sympatric species (Adams & Rohlf, 2000), environmental variables such as temperature and rainfall (Benítez et al, 2014), temporal variation (Drake & Klingenberg, 2008), and geographic variation (Lashkari et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…longipalpis species complex is accepted and has raised the prospect of assigning valid taxonomic names to its included species ( Brandão-Filho et al 2009 ). Although a few morphologic studies have shown differences among some populations (de la Riva et al 2001 , Santos et al 2015 ), no discrete anatomical attribute has proven to be reliably diagnostic and extensively employed. The exact number of sibling species in the Lu.…”
mentioning
confidence: 99%
“…Other studies have also been unable to separate the sibling species within this group. Santos et al (2015) found no significant morphometric differences when comparing L. longipalpis and L. cruzi populations from the Brazilian state of Mato Grosso do Sul. In addition, Pinto et al (2015) demonstrated that these species are highly related and present low genetic divergence.…”
Section: Discussionmentioning
confidence: 62%
“…Santos et al . () found no significant morphometric differences when comparing L. longipalpis and L. cruzi populations from the Brazilian state of Mato Grosso do Sul. In addition, Pinto et al .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation